Investigation of Photocatalytic Activity of TiO2/SiO2Nanocomposite in Presence of Carboxy Methyl Cellulose, Poly(vinyl pyrrolidone) and Hydroxyl Propyl Cellulose - Moradi, S.; Aberomand Azar, P.; Khodadadi, B. (Asian Journal of Chemistry, 2012)
TiO2/SiO2 nanocomposites powder are the most important materials due to their extensive application in the field of photocatalysis, were prepared by the sol-gel method with and without poly(vinyl pyrrolidone), carboxy methyl cellulose and hydroxyl propyl cellulose as additives. In this work, the influence of these additives on the properties, structure and photocatalytic activity under UV-irradiation for removal of organic pollutant were investigated by IR spectra, scanning electron microscopy, energy dispersive analytical X-ray and X-ray diffraction methods. The results suggest that these additives play an important role in decreasing of particles size and TiO2/SiO2 with hydroxy propyl cellulose was the best sample.